The Role of Corporate Governance and Size of the Firm on Internal Control Disclosure - Abdul Manap; Mohamad Ramadhan Agung Nugroho; Asep Saepullah; Yusnidar; Atik Sekianti (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
This study examines how internal control disclosure is impacted by corporate governance and firm size. The size of the board of commissioners, the makeup of the independent board of commissioners, management vs institutional ownership, the size of the audit committee, and the degrees in accounting or finance held by audit committee members are all factors in corporate governance. The study's sample is the portion of the banking sector that was traded on the Indonesia Stock Exchange between 2015 and 2021. In this study, 29 companies were included in the sample, and observations were made over a period of 7 years. Purposeful sampling was employed as the sampling approach. To process their data, researchers employ multiple regression analysis. The findings of this study suggest that internal control disclosures are influenced by firm size and level of accounting or finance education. Internal control disclosures are unaffected by the size of the audit committee, the make-up of the independent board of commissioners, management ownership, institutional ownership, or the number of commissioners.